Divining the self a study in Yoruba myth and human consciousness - Love, Velma E., 1949- (University Park, Pa. : Pennsylvania State University Press, 2012)
"Explores the dynamics of African American engagements with the Holy Odu, the unwritten sacred scriptures of the West African Ifa Orisha tradition. Examines the experiences of selected practitioners, focusing on the ways in which the divinatory narrative and associated mythology impact self-understanding and worldview"--
Mythic origins and cultural practices -- Orisha archetypes, cultural memory, and the Odu -- Divining the self -- Symbols and signposts for the journey -- Powers of the mothers -- Oshun, Yemonja, and Oya.
Includes bibliographical references (p. [131]-134) and index.
Description based on print version record.
Keywords: African Americans -- Religious life; Yoruba (African people) -- Religion -- Influence; Ifa (Religion) -- United States; Orishas; RELIGION / Ethnic & Tribal; Electronic books